Non-Invasive Study: Monitoring the Heart Rate and SpO2 of the New Born using InfaWrap Device - Mohd Hanafi, Abdul Rahim; Mohd Azrul Hisham, Mohd Adib; Mohamad Zairi, Baharom; Idris, Mat Sahat; Nur Hazreen, Mohd Hasni (IEEE, 2021)
Nowadays, the non-invasive method in the newborn healthcare system has become a top priority for effective treatment. The InfaWrap device is the first product that has been developed to help parents monitor their babies using non-invasive methods. In this paper, the Infa Wrap device was used to investigate the baby's heart rate, SpO 2 , and body temperature. This study focused on neonates without any chronic diseases. In this study, a female baby with 3 months 7 days old, with a height is 56.2 cm, and 6.2 kg has been tested. This test was taken 10 minutes in the morning, afternoon, and night in three different conditions: normal, sleep, and awake. The observation result presented here indicates that the accuracy performance of the Infa Wrap device is stable. Although the sensors used are minimally technologies but have limitations mainly due to the baby feet' movement.